AMPK Activation Alleviates Myocardial Ischemia-Reperfusion Injury by Regulating Drp1-Mediated Mitochondrial Dynamics - Du, Jingxia; Li, Hongchao; Song, Jingjing; Wang, Tingting; Dong, Yibo; Zhan, An; Li, Yan; Liang, Gaofeng (Frontiers in Pharmacology, 2022)
Myocardial ischemia/reperfusion injury (MIRI) is a life-threatening vascular emergency following myocardial infarction. Mitochondrial dysfunction, defined as disordered mitochondrial dynamics, is a salient feature of MIRI, while the potential mechanism is still unclear. This study sought to explore whether Adenosine monophosphate-activated protein kinase (AMPK) activation could alleviate MIRI by regulating GTPase dynamin-related protein 1(Drp1) mediated mitochondrial dynamics. Isolated mouse hearts were subjected to ischemia/reperfusion (I/R) treatment in a langendorff perfusion system, and H9C2 cells were subjected to hypoxia /reoxygenation (H/R) treatment in vitro. The results of isolated hearts showed that AICAR, the AMPK activator, could significantly improve left ventricular function, decrease arrhythmia incidence and myocardial infarction area. Meanwhile, AICAR caused an increase of superoxide dismutase (SOD) and a decrease of malondialdehyde (MDA) content in myocardial homogenate. Furthermore, molecular biological results showed that AICAR inhibited phosphorylation of Drp1(Ser 616) and enhanced phosphorylation of Drp1(Ser 637), and at the same time，AICAR reduced the expression of inflammatory cytokines (TNF-ɑ, IL-6, and IL-1β) and mitochondrial fission genes (Mff, Fis1), improved the expression of mitochondrial fusion genes (Mfn1, Mfn2). In the cell experiment, trends were similar to those seen in animal experiments. AICAR improved mitochondrial membrane potential (MMP), reduced reactive oxygen species (ROS) production and inhibited mitochondrial damage. To further prove if Drp1 regulated mitochondrial dynamics mediated AMPK protection effect, we used the mitochondrial fission inhibitor Mdivi-1. The results showed the same trends as AICAR in H9C2 cells, Mdivi-1 significantly improved MMP, inhibited ROS production, reduced the expression of TNF-a, IL-6, IL-1β, Fis1 and Mff, and improved the expression of Mfn1 and Mfn2. Further research confirmed that AMPK inhibitor Compound C couldn’t reverse the protection effect of Mdivi-1. In conclusion, this study confirmed that activation of AMPK exerted the protective effects of MIRI, which was largely dependent on the inhibition of Drp1 mediated mitochondrial fission.